Reflexão sobre pesquisa colaborativa: articulações escola e universidade (Ciência do Sistema Terra, Currículo e Formação de Professores) - Gonçalves, Pedro Wagner; Sicca, Natalina Aparecida Laguna; Fernandes, Maria Cristina da Silveira Galan; Alves, Maurílio A. Ribeiro; Fernandes, Silvia Aparecida de Sousa [UNESP] (My University, 2013)
This work was born from public presentation done during 8th Meeting in High Level Education Program at University Moura Lacerda, Ribeirão Preto, SP, Brazil, in October 2012. That time showed up theoretical hypothesis of teacher education done by a collaborative research group of teachers and researchers and main results for Pedagogy course and students of basic levels. This paper intends to show up the findings of researches done by group of studies for Earth System Science and teacher education. The aim is to think about curriculum politics and teacher education from teachers’ practices, researches and studies on high school level. Moreover, we show up theoretical fundamentals which guide our actions and think. After we treat of organization, results and curricular innovations guided by Earth System Science and how that changes the view of nature of teachers and students. Qualitative methods of research help to describe curricular processes collectively done together with teachers of public schools. Our findings show up that teacher education must be a long, collective and interactive process to prepare high level teachers and researchers for teaching and teacher education.

Este artigo é resultado de pesquisas realizadas no interior do Grupo de Estudos de Ciência do Sistema Terra e Formação de Professores e tem por objetivo refletir sobre currículo e formação de professores a partir das experiências de ensino e pesquisa. Apresenta, inicialmente, os fundamentos teóricos que orientam as ações e reflexões do grupo de pesquisa. Em seguida, discorre sobre a organização e os produtos do grupo de pesquisa, com ênfase em propostas de inovação curricular no ensino médio e no ensino superior, tendo como eixo o ensino de Ciência do Sistema Terra, as concepções de Natureza e as inovações educacionais promovidas no interior do grupo de pesquisa.
Keywords: Ensino básico; Geociências; Formação de Professores